2015
DOI: 10.1103/physrevb.92.035444
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, diffusion, and vibration of oxygen onAg(110)

Abstract: We have employed ab-initio density functional theory (DFT) to study the adsorption, dissociation, diffusion, and vibration of oxygen on Ag(110). We find that the four-fold hollow site is the preferred site 68.43.Jk, 68.43.Pq

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 67 publications
6
25
0
Order By: Relevance
“…At variance with our conclusions, Hahn and Ho [43] indicated that S features were related to O adatoms at hollow and short-bridge (SB) sites, which were generated by dissociating chemisorbed O 2 with voltage pulses at 13 K. Oxygen at the SB site was said to generate a two-lobe rather than a circular feature, and to be able to jump from one SB to another on a neighbouring row without falling into the much deeper potential wells in-between. Our STM simulations indicate, however, that O adatoms at SB sites should appear as protruding features in the STM image with ~1 Å of height from the surface (not shown here), but also that this site is unstable with respect to lateral displacements [48]. The results of ref.…”
Section: Simulated Stm Images 11 Isolated O Adatomsmentioning
confidence: 47%
See 2 more Smart Citations
“…At variance with our conclusions, Hahn and Ho [43] indicated that S features were related to O adatoms at hollow and short-bridge (SB) sites, which were generated by dissociating chemisorbed O 2 with voltage pulses at 13 K. Oxygen at the SB site was said to generate a two-lobe rather than a circular feature, and to be able to jump from one SB to another on a neighbouring row without falling into the much deeper potential wells in-between. Our STM simulations indicate, however, that O adatoms at SB sites should appear as protruding features in the STM image with ~1 Å of height from the surface (not shown here), but also that this site is unstable with respect to lateral displacements [48]. The results of ref.…”
Section: Simulated Stm Images 11 Isolated O Adatomsmentioning
confidence: 47%
“…we have carried out density functional theory based calculations to obtain the following for various configurations of the O/Ag(110) system: relaxed (ionically) geometry, energetics and activation energy barriers of several relevant phenomena (adsorption, vacancy formation, diffusion), and simulated STM images. Note that these detailed results have not been reported in our earlier publication [48]. We discuss first the simulated STM images.…”
Section: B Dft and Kmc Simulationsmentioning
confidence: 85%
See 1 more Smart Citation
“…The charge transfer correlates well with increasing the O−O distance in the oxygen molecule. These findings are consistent with the results of DFT calculations, indicating that the value of charge transfer from a pure Ag(110) surface to an O 2 molecule depends on its position . The maximum value was approximately 0.9e, which is lower than in the case of the h ‐BN/AgNP interface.…”
Section: Resultsmentioning
confidence: 99%
“…Dissociation of O 2 with production of two O atoms is exothermic with an energy barrier of 0.42 eV [38]. Our Kinetic Monte Carlo (KMC) simulations show that this process is peaked around 157 K (Fig.…”
Section: Ag-o Unit On Ag(110): A) Pristine Surface; B) the Dissociatementioning
confidence: 96%